CULTURAL MEANINGS OF FORWARD AND REVERSE PERSPECTIVES IN FINE ART - Maxim S. Lytov (Russian Studies in Culture and Society)
The relevancy of addressing the problem of forward and reverse perspective in the depiction of space on the plane when teaching drawing to children and students is due to the dominance of geometric stereotypes in their pictures, reflecting the photographic character of the surrounding video environment.